Stability Analysis of GNSS Stations Affected by Samos Earthquake - Ozarpaci, Seda (MDPI, 2024)
An earthquake cycle can cause meters of displacement on the surface and at Global Navigation Satellite System (GNSS) stations. This study focuses on the identification of GNSS stations that have significant displacement because of a Mw 7.0 earthquake near Samos Island on 30 October 2020. The S-transformation method is used to examine 3D, 2D and 1D coordinate systems along with threshold and statistical test approaches. The highest coseismic offset among the 21 GNSS stations is displayed by SAMO, and CESM, MNTS, IZMI and IKAR also experience significant displacement. Significantly displaced stations are successfully identified in both 3D and 2D analyses. In the up component, SAMO is the only unstable station. The coordinate S-transformation method can be used in detecting unstable points in a GNSS network and provide valuable information about the effects of an earthquake on GNSS stations.
Keywords: coordinate S-transformation; hypothesis test; threshold approach; Samos earthquake; SPLIT FUNCTIONAL-MODEL; DEFORMATION; PARAMETERS; FIELD; IZMIT; Chemistry; Engineering; Materials Science; Physics